Sanksi Pidana Terhadap Penggunaan Telepon Seluler Saat Mengemudi Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Husnaini (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
The development of transportation, especially traffic transportation on the road, has both positive and negative impacts. One of the negative impacts is the frequent occurrence of traffic violations. According to Perinkins in Nur Fitriyani, traffic is a relationship with transportation and property on the road and includes travel, movement of vehicles, withdrawal of movable objects, passenger transportation, pedestrian flow, and coupled with several activities related to road use. general. What are the factors that cause the use of cell phones while driving? Is the criminal sanction against the use of cellular phones while driving based on Law No. 22 of 2009 concerning Road Traffic and Transportation. This study uses a normative juridical research method. factors that cause drivers to commit violations in the form of using a telephone while driving a vehicle. Lack of public awareness of these traffic violations. The public's ignorance of the existence of sanctions for drivers who use the phone while driving. As drivers, obey the existing traffic rules. In driving we should bring the equipment of our vehicle. In driving a vehicle, it is best not to commit violations that will endanger our own safety as drivers and the safety of others.